Performance implications of core and complementary pre-entry experience: The role of consumer heterogeneity in mobile telephony - JP Eggers; Michał Grajek; Tobias Kretschmer (European School of Management and Technology (ESMT), 2012)
We study how two distinct types of pre-entry experience core technological experience and market-based complementary experience affect post-entry performance in a new industry. We focus on the fit between capabilities generated through pre-entry experience and the preferences of heterogeneous consumer segments. Specifically, we suggest that firms with pre-entry experience in the focal technology will attract more valuable consumers, but as these consumers typically make adoption decisions early the firm must enter early to benefit. Conversely, firms with pre-entry experience in the focal market will attract a larger share of less valuable consumers regardless of entry timing. Our empirical analysis of the global 2G mobile telecommunications industry supports our theory and provides important insights for research on experience and entry dynamics in high-technology industries.
urn:nbn:de:101:1-201206287172
Keywords: C51; L10; O33; 650; pre-entry experience; mobile telecommunications; consumer segments; complementary assets; core technical knowledge